ACS Chemical Neuroscience Molecule Spotlight on Valdoxen - Hopkins, Corey R. (American Chemical Society, 2010)
[Image: see text] A new and novel non-SSRI potential treatment option for major depressive disorders is Valdoxen (agomelatine) which is currently in phase III clinical studies. Valdoxen is a norepinephrine disinhibitor (NNDI) and is also an antagonist of the 5-HT(2C) receptor.